Farmers' management of sustainable highland land use with rotational shifting cultivation - Yimyam N. (2017)
Highland agriculture in Thailand has traditionally been dominated by subsistence production with shifting cultivation. However, there is increasing economic integration with cash crops in many highland villages, which has resulted in the reduction of forest cover and agricultural biodiversities. This paper describes studies of how traditional land use system of a highland village of Tee Cha village, Sob Moei sub-district, Sob Moei district, Mae Hong Son province affects agricultural productivity and conservation of biological diversity of natural and agricultural resources. In this Karen village farmers practiced traditional 7 year rotation of upland rice with a tree called Pada (Macaranga denticulata) as the primary species during the fallow period. The system was managed both communally and at the family levels, governed by sets of rules and custom. Households manage their own crops, however most farming activities were done by exchanged labor. For management of forest areas, including fallow forests in between cropping periods, care and conservation of forest resources are based on communal agreements and rules, backed rituals. For management of plant genetic resources, the farmers maintained a biologically diverse germplasm of agricultural species, many of which in many different varieties. The study has revealed that this land use practice of agrobiodiversity management in this highland village focusing on subsistent farming with the aim to provide food security for its members, also has an important function in conservation. The village helps to preserve in situ biological diversity of agricultural germplasm and wild species while maintaining a substantial forest area.